Understanding Programming Language Semantics For The Sophisticated World - Wu, Trong (IAENG international journal of computer science, 2009)
Computer is used virtually everywhere everyday in the world. Before 1990s computer systems are generally used for mathematics, engineering, and business computations. In this period, mainly use FOTRAN, COBOL, and PL/1 for computation on mainframe systems. In the last two decades scientists found that the natural world is complicated that has overwhelmed with data that required more sophisticated computation facilities and better languages for computation and that created new computing disciplines. This paper addresses the understanding of programming language semantics that will help user in selection of programming language features for various applications needs and that can help programmers in designing reliable, accurate, efficient, and user-friendly software systems for the sophisticated word.